Authentication of organic pork and identification of geographical origins of pork in four regions of China by combined analysis of stable isotopes and multi-elements. (July 2020) - Zhao, Yan; Tu, Ting; Tang, Xiaoyan; Zhao, Shanshan; Qie, Mengjie; Chen, Ailiang; Yang, Shuming
Abstract: The purpose of this study was to verify that the organic status of pork purchased in the markets from four different regions of China can be authenticated by the combined analysis of stable isotopes and multiple elements. Four stable isotope ratios (δ 13 C, δ 15 N, δ 2 H and δ 18 O) and the concentrations of seven elements (K, Na, Mg, Ca, Fe, Cu and Se) were determined in organic and conventional pork samples from four locations of China. Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA) were used to analyze stable isotope ratios and multi-element concentrations in pork. Based on the limited database of analytical values, the methodology would be potentially able to confirm whether a sample of pork came from the region and organic status it claimed. These results provide a possibility for authenticity of organic agricultural products from a large scope such as a province even a country. Highlights: Stable isotopes and multi-elements in conventional and organic pork were analyzed. Organic pork was authenticated well by stable isotopes and multi-elements analysis. Pork origin was verified by stable isotopes and multi-elements analysis.